Performance of different crop species with pointed gourd (Trichosanthes dioica Roxb.) (Bangladesh Journal of Agricultural Research, 2013)
The experiment was conducted at the Regional Agricultural Research Station, Jessore during the period from November 2008 to April 2010 to find out the suitable component crop and planting system under intercropping system with pointed gourd for higher yield and economic return. The treatment combinations were T1 = Pointed gourd (PG) sole, T2 = PG + radish + mungbean (1 row at the boarder of the bed) + amaranth (broadcast), T3 = PG + radish + mungbean (2 rows at the boarder of the bed) + shabuj shak (broadcast), T4 = PG + radish + Indian spinach (1 row at the boarder of the bed), T5 = PG + radish + Indian spinach (2 rows at the boarder of the bed) and T6 = PG + radish + mungbean: Indian spinach (1 : 1 row at the boarder of the bed). The fruit yield (26.27-30.50 t/ha) of pointed gourd did not affect by sole and different intercropping systems. The highest pointed gourd equivalent yield (68.02 t/ha), gross return (Tk.1020300/ha) and net return (Tk.631466/ha) and benefit cost ratio (2.62) was obtained from the intercropping combination of PG + radish + Indian spinach (2 rows at the boarder of the bed). DOI: http://dx.doi.org/10.3329/bjar.v38i3.16979 Bangladesh J. Agril. Res. 38(3): 523-529, September 2013